Prevention of Ovarian Hyper stimulation Syndrome by using gonadotrophic releasing hormone analogue to induce final ovulation trigger in invitro fertilization cycles - Sultana, Safia; Sultana, Misbah; Ashraf, Shazia; Khan, Muhammad (Journal of Rawalpindi Medical College, 2023)
Objectives: To find out occurrence of ovarian hyperstimulation in patients who were hyper responders in in vitro fertilization cycles. Secondary outcome was to assess number of metaphase II oocyte and fertilization rate, cleavage rate and pregnancy outcome when GnRHa is used for final maturation and triggering ovulation. STUDY DESIGN, SIZE, and DURATION: This is retrospective descriptive analysis of cases managed at single center from June 2017 till May 2018. PATIENTS & METHODS: Twenty patients were identified as hyper responders based on baseline, ovarian reserve characteristics, that is antral follicle count, (AFC) > 25, AMH > 4ng/ml and on day of trigger, follicles >-25 in number of ≥ 11mm were administered GnRHa trigger and 1500IU hCG on oocyte retrieval day while luteal phase was supported with daily vaginal progesterone and twice daily estradiol valerate. Sixteen patients underwent fresh transfer while four patients had their embryos frozen. MAIN RESULTS: Twenty patients were identified as high risk and their baseline characteristics were, mean age 31.7 ± 4.50, mean antral follicle count 25.7 ± 5.01, Anti Mullerian hormone level mean 4.64 ± 2.52 and PCOS was present in 35% cases. Peak estradiol level mean 13455-± 6632pmol/l and mean follicles count of 25.45 ± 8.78 confirmed a high response. Oocyte yield was 11.45+ Metaphase oocyte retrieved were 85.5% and cleavage rate of 93%. No case of early onset OHSS was identified. Only one patient developed moderate OHSS. Pregnancy rate was 31.25%. Miscarriage rate was 6.3% and ongoing pregnancy was 25%. CONCLUSION: This small retrospective descriptive analysis supports the view of current literature that GnRH trigger not only prevents early onset OHSS also achieves increase of M11 oocytes. In addition, pregnancy outcome is not statistically different to those cycles where hCG is used as trigger.